INDONESIAN THROUGHFLOW TRANSPORT VARIATIONS AND OCEANOGRAPHIC’S PARAMETER IN TIMOR SEAS AS AN INDICATION OF ENSO EVENTS - M. Safitri; S. Y. Cahyarini; M. R. Putri (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Variation of Indonesian Throughflow transport, salinity, and temperature at surface level of Timor Seas monthly, seasonal, and annual mean scale was studied using the datasets provided by IRI/LDEO Climate Data Library i.e Simple Ocean Data Assimilation (SODA) for the salinity. The period data used in this study was 1995-2004, ERSST for the temperature. The Indonesian Thourghflow transport was obtained from Hautala et al. (2001). Result of this study showed there was influence of monsoon and ENSO on oceanographic parameters. During the South East (SE) monsoon, an emptiness on the surface water occurred in Timor Seas due to the easterly wind, which causes the upwelling. The results was also shown that during the SE monsoon the average temperature was 26.84oC, salinity was 34.35, and Indonesian Throughflow transpor was -0.34 Sv. While during the North Western (NW) monsoon the average temperature was 29.6 oC, salinity was 34.22, and the Indonesian Throughflow transport was -0.27 Sv. The negative value (-) means that the flow toward the Indian Ocean. In addition, based on temporal correlation between Indonesian Throughflow transport and NINO 3.4 index was found that the annual mean variability increases (-0.18 Sv) during La Niña period and decreased (-0.13 Sv) during period El Niño. These indicated that ENSO phenomena influenced the transport across the Equatorial Pacific east-west. Keywords: Indonesian throughflow, salinity, temperature, SODA, Monsoon, ENSO, Timor Seas.